The Development and Practice of Small Hydropower Clean Development Mechanism Projects in China - Heng, Liu; Xiaobo, Hu (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
This paper generally describes the background of global hydropower CDM projects and the development of Small Hydropower (SHP) CDM projects in China. It analyses the features of China SHP CDM projects, and summarize their prospect and future challenges. DOI: http://dx.doi.org/10.3126/hn.v8i0.4900 Hydro Nepal Issue No. 8, 2011 January Page: 8-13 Uploaded date: 16 June, 2011